Simulation of Active Filtering Applied to A Computer Centre - Sentosa Setiadji, Julius; Hosiana Tumbelaka, Hanny (Jurnal Teknik Elektro, 2002)
In this paper, the implementation of a shunt active power filter with a small series reactor for a three-phase system is presented. The system consists of computer loads, which are harmonic voltage sources, with significant unbalanced components. The filter consists of a three-phase current-controlled voltage source inverter (CC-VSI) with a filter inductance at the AC output and a DC-bus capacitor. The CC-VSI is operated to directly control the AC grid current to be sinusoidal and in phase with the grid voltage. The simulation results indicate that the filter along with the series reactor is able to handle the harmonic voltage sources, as well as the unbalance, so that the grid currents are sinusoidal, in phase with the grid voltages and symmetrical. Abstract in Bahasa Indonesia : Dalam makalah ini dijelaskan tentang penggunaan filter aktif type paralel dengan menggunakan reaktor kecil yang dipasang secara seri untuk sistem tiga phasa. Jaringan sistem ini menggunakan komputer sebagai beban yang merupakan sumber harmonisa tegangan; sekaligus menimbulkan ketidakseimbangan sistem. Filter daya aktif merupakan current-controlled voltage source inverter (CC-VSI) tiga phasa dengan sebuah filter induktansi pada keluaran AC dan sebuah kapasitor DC-bus. CC-VSI dioperasikan untuk mengendalikan secara langsung arus jala-jala AC menjadi sinusoidal dan sephasa dengan tegangan jala-jala. Hasil simulasi menunjukkan bahwa filter dengan reaktor seri mampu untuk mengatasi sumber harmonisa tegangan dan juga ketidakseimbangan beban sehingga gelombang arus menjadi sinusoidal, sephasa dengan tegangan jala-jala dan simetris Katakunci: filter daya aktif, distorsi harmonik.